Peritoneal dialysis exit-site leak complicated by peritoneal dialysis-related peritonitis due to Actinomyces neuii. Issue 5 (8th October 2015) - El Kossi, Mohsen M.; Darwish, Sanaa Fadel; Agwuh, Kenneth; Milupi, Manyando
Abstract : Introduction: Actinomyces neuii is a rare cause of peritoneal dialysis-related peritonitis. Case presentation: A 66-year-old male had end-stage renal disease on peritoneal dialysis treatment for 30 months. He developed exit-site leak with infection. Diphtheroids were isolated and considered initially as skin commensals. Dialysis treatment was suspended and on reinstitution he developed peritoneal dialysis-related peritonitis. The organism isolated from the peritoneal dialysis fluid was A. neuii . Conclusion: This case was treated successfully with peritoneal dialysis catheter removal and oral amoxicillin.